The Impact of Pre-analytical Quality Initiatives on Cholangiocarcinoma Diagnostics in Thailand - Koonmee, Supinda; Sangkhamanon, Sakkarn; Intarawichian, Piyapharom; Aphivatanasiri, Chaiwat; Kunprom, Waritta; Sa-ngiamwibool, Prakasit; Balthaisong, Suwit; Phuyao, Chitsakul; Prajumwongs, Piya; Alaghehbandan, Reza; Thanee, Malinee (Frontiers in Public Health, 2022)
Cholangiocarcinoma (CCA) is the most prevalent malignancy in Thailand, with unfortunate late diagnosis and frequent metastatic disease outcome. An accurate tissue diagnosis is the first and most important step in treatment of CCA. Tissue quality and preservation during pre-analytical phase play a major role in proper histological evaluation and potential biomarker testing. This study evaluated the impact of using “Cholangiocarcinoma Screening and Care Program (CASCAP)” container, as an innovative tool to address pre-analytical challenges pathology laboratories face in Thailand. This is a comparative study examining the quality of CCA specimens between utilizing CASCAP container versus conventional method, using H&E and immunohistochemistry. CCA tissue quality using CASCAP container significantly reduced artifact deposition, while improved cellular structure, nuclear and cytoplasmic morphologies. The immunohistochemical expression of CK19, a prognostic marker in CCA, significantly improved in the CASCAP container group compared with the conventional method. This innovation is proven to significantly enhance the CCA tissue quality diagnostics and prognostic biomarker testing, hence improving overall cancer care diagnosis and treatment in Thailand.